Crosstalk events in the estrogen signaling pathway may affect tamoxifen efficacy in breast cancer molecular subtypes. (December 2015) - de Anda-Jáuregui, Guillermo; Mejía-Pedroza, Raúl A.; Espinal-Enríquez, Jesús; Hernández-Lemus, Enrique
Abstract : Highlights: A methodological pipeline to analyze enrichment in crosstalking pathways implicated in phenotypes of interest is presented. The aforementioned pipeline is used to explore deregulation of pathways crosstalking with the estrogen signaling pathway in breast cancer samples of different molecular subtypes. Exploration of enrichment lead to the generation of hypothesis related to the influence of crosstalking pathways to resistance to anti-estrogenic drugs. Abstract: Steroid hormones are involved on cell growth, development and differentiation. Such effects are often mediated by steroid receptors. One paradigmatic example of this coupling is the estrogen signaling pathway. Its dysregulation is involved in most tumors of the mammary gland. It is thus an important pharmacological target in breast cancer. This pathway, however, crosstalks with several other molecular pathways, a fact that may have consequences for the effectiveness of hormone modulating drug therapies, such as tamoxifen. For this work, we performed a systematic analysis of the major routes involved in crosstalk phenomena with the estrogen pathway – based on gene expression experiments (819 samples) and pathway analysis (493 samples) – for biopsy-captured tissue and contrasted in two independent datasets with in vivo and in vitro pharmacological stimulation. Our results confirm the presence of a number of crosstalk events across the estrogen signaling pathway with others that are dysregulated in different molecular subtypes of breast cancer. These may be involved in proliferation, invasiveness and apoptosis-evasion in patients. The results presented may open the way to new designs of adjuvant and neoadjuvant therapies for breast cancer treatment.